Using adaptive runtime filtering to support an event‐based performance analysis. (24th February 2017) - Stolle, Jonas; Wagner, Michael; Doleschal, Jens; Schmitt, Felix; Brunst, Holger
Summary: Event‐based performance monitoring and analysis are effective means when tuning parallel applications for optimal resource usage. In this article, we address the data capacity challenge that arises when applying the tracing methodology to large‐scale parallel applications and long execution times. Existing approaches use static, pre‐defined event filters to reduce the performance data to a manageable size. In contrast, we propose self‐guided filters that automatically adapt to an application's runtime behaviour and therefore, do not require any previous knowledge or application executions. Our contribution consists of four adaptive runtime filters, which target a specific type of data redundancy each. The filters focus on detecting identical events in loop iterations, constant events with no variation in time, and very short, highly frequent, typically not very meaningful events, having a severe impact on the total data volume. We evaluate our prototype implementation with five real‐world applications and achieve a data reduction of two orders of magnitude while increasing execution time less than 1%. Likewise, we show that the qualitative impact of our filters on performance analysis in state‐of‐the‐art analysis tools can be reduced by adding feedback methods and statistical information to the filtered traces. Copyright © 2017 John Wiley & Sons, Ltd.